2013
DOI: 10.3892/ijo.2013.2208
|View full text |Cite
|
Sign up to set email alerts
|

PRDX1 and PRDX6 are repressed in papillary thyroid carcinomas via BRAF V600E-dependent and -independent mechanisms

Abstract: Many clinical studies highlight the dichotomous role of PRDXs in human cancers, where they can exhibit strong tumor-suppressive or tumor-promoting functions. Recent evidence suggests that lower expression of PRDXs correlates with cancer progression in colorectal cancer (CRC) or in esophageal squamous carcinoma. In the thyroid, increased levels of PRDX1 has been described in follicular adenomas and carcinomas, as well as in thyroiditis, while reduced levels of PRDX6 has been found in follicular adenomas. We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…PRDX6 presented reduced levels in papillary thyroid carcinomas compared to non-neoplastic tissues. A correlation between the presence of lymph node metastasis and low PRDX6 levels was also described [60]. The progression from low-grade to high-grade prostate carcinoma and metastases is mediated by down-regulation of the androgen receptor target genes, including DHCR24 (24-Dehydrocholesterol Reductase) [61].…”
Section: Discussionmentioning
confidence: 99%
“…PRDX6 presented reduced levels in papillary thyroid carcinomas compared to non-neoplastic tissues. A correlation between the presence of lymph node metastasis and low PRDX6 levels was also described [60]. The progression from low-grade to high-grade prostate carcinoma and metastases is mediated by down-regulation of the androgen receptor target genes, including DHCR24 (24-Dehydrocholesterol Reductase) [61].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a marked reduction in PRDX6 levels has been demonstrated in a cohort of PTCs (75). Taken together, all these studies have demonstrated that PRDX6 has a pro-tumorigenic function, promoting cell proliferation by its peroxidase activity, and facilitating invasiveness by means of its PLA2 activity (150).…”
Section: Prdxs In Tumorigenesismentioning
confidence: 96%
“…Decreased PRDX1 levels in papillary thyroid carcinomas (PTCs) (74) correlate with the presence of the BRAF V600E mutation and of lymph node metastasis, suggesting that PRDX1 reduction may be caused by mutated BRAF, and this is associated with a more aggressive clinical outcome of PTCs (75). …”
Section: Prdxs In Tumorigenesismentioning
confidence: 99%
“…However, Nicolussi A et al . have demonstrated that PRDX1 and PRDX6 are reduced in papillary thyroid carcinomas by BRAF V600E‐dependent and ‐independent mechanisms 117. Additionally, down‐regulation of PRDX1 suppresses growth and promotes apoptosis in bladder cancer cells through NF‐kB signalling pathway after Bifidobacterium infantis thymidine kinase/nucleoside analogue ganciclovir (BI‐TK/GCV) treatment 118.…”
Section: Prdx1 and Other Types Of Malignancymentioning
confidence: 99%